Calceolaria ascendens subsp. exigua, comb. et stat. nov. (Calceolariaceae), endémica de la cordillera de la Costa de Chile central - García , Nicolás (Gayana Botánica, 2010)
The new combination Calceolaria ascendens Lindl. subsp. exigua (Witasek) Nic.García is made based on material collected at Central Chile’s Coastal mountain range, around parallel 33º S. The new subspecies inhabits rock crevices at the high mountain between 1,600 and 2,100 m a.s.l.